The breeding biology of Mute Swans Cygnus olor in southeast Cork, Ireland - Smiddy, Patrick; O'Halloran, John (Wildfowl, 1991)
The breeding success of Mute Swans nesting in southeast Cork Ireland, from 1972-89 is analyzed. Data from 151 nests are presented. Eight percent of pairs that built nests failed to lay eggs. Mean final clutch size was 5.5 eggs. Seventy-one percent of clutches hatched successfully. The mean brood size at fledging was 3.8 per clutch. No significant difference was found in the mean number of cygnets produced per clutch across habitat types. The mean clutch size was lower, and the number of cygnets fledging per clutch higher than reported in most studies.